An extensive review on implantable antennas for biomedical applications: Health considerations, geometries, fabrication techniques, and challenges - Mosab Jasim; Ahmed Jamal Abdullah Al-Gburi; Mehwish Hanif; Zaheer Ahmed Dayo; Mohd Muzafar Ismail; Zahriladha Zakaria (Alexandria Engineering Journal)
Implantable medical devices (IMDs) are revolutionizing healthcare by enabling continuous monitoring, targeted treatment, and improved quality of life for patients with chronic conditions. Among the critical components of IMDs are implantable antennas, which facilitate reliable wireless communication for various biomedical applications, including real-time health monitoring and therapeutic interventions. The design and development of these devices present significant challenges, such as stringent miniaturization requirements, specific absorption rate (SAR) regulations, biocompatibility concerns, and the need for low power consumption to extend device longevity. This paper provides a comprehensive review of implantable medical device technologies, with a particular emphasis on implantable antennas. It highlights recent breakthroughs and novel contributions that address these complex challenges, offering a detailed analysis of advancements in antenna structures, radiation properties, and performance optimization. Key innovations in enhancing miniaturization, radiation efficiency, bandwidth, and gain are thoroughly discussed, along with the integration of advanced materials and fabrication techniques to achieve high performance while ensuring patient safety. Moreover, this paper underscores the critical importance of regulatory compliance, patient safety, and biocompatibility in the development of IMDs. Meeting these stringent standards is essential to ensure that IMDs operate safely and effectively within the human body over extended periods. By providing an in-depth review of state-of-the-art solutions and identifying emerging trends, this paper serves as an invaluable resource for researchers, engineers, and medical practitioners involved in the design and deployment of implantable medical devices. It aims to foster further innovation in the field, ultimately contributing to the creation of more sophisticated, reliable, and effective implantable medical technologies that enhance patient care and treatment outcomes.